The electrical properties of TiO₂/Dye/CuI Solar Cell at different concentration of CuI as the hole conductor: article / Siti Zawani Roslan and Norulhuda Abd Rasheid - Roslan, Siti Zawani; Abd Rasheid, Norulhuda (2013)
This research focusses on the performence of solid-state dye-sensitized solar cell by varying the molar concentration of CuI thin film as hole conductor. Nanoporous semiconductor TiO₂ acted as ntype in solid-state dye-sensitized solar cell which is deposited with dye to absorb the light The correlation between thicknesr ofthe thin lilm and the efiiciency of solar cell was investigated. The incomplete pores filling of TiO2 teads to the bed efliciency due to the increase in recombination and series resistance in solar cell. Thus, mister rtomizer method was used to increase the pores Iilling of TiO₂. The result shows the thickness of thin film and perticle size of CUI increase as the molar concentration increases. The efficiency of solid-state DSSC is strongly related to the thickness thin film, filling fraction of TiO₂, and the photon absorption of dye.